Faktor motivasi dalam amalan pembelajaran hafazan al-Quran - Ali Hasan Ahmad Rozaini, Mohd Patel Iza Faradiba, Abd Ghani Abd Rahman, (Universiti Pendidikan Sultan Idris, 2017)
Faktor motivasi dalam amalan pembelajaran hafazan al-Quran by Ali Hasan Ahmad Rozaini, Mohd Patel Iza Faradiba, Abd Ghani Abd Rahman,